(3eYGde GdOjf hedGc GdeLJgOjfs - (3,GdMSf Hf Rjf GdOjf (B((3GdTgjO GdKGfj(B) (3GHf Ydj Hf CMeO GdTGej GdYGedj, CHh efUhQ , GHf GdTgjO GdKGfj,J (B1011 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Chdi eG GfabJ ai JMUjdg cfhR GdCYeGQ s
(3BNQgG (B:s
(3hPdc cGa ai GdJQLjM Je bSe GdCUhd ef cJGH eYGde GdOjf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B227s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B505s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CUhd abg (B35(3e(B) s
Keywords: (3CUhd Gdabgs